2021
DOI: 10.12688/f1000research.19931.4
|View full text |Cite
|
Sign up to set email alerts
|

Are adverse effects of cannabidiol (CBD) products caused by tetrahydrocannabinol (THC) contamination?

Abstract: Cannabidiol (CBD)-containing products are widely marketed as over the counter products, mostly as food supplements. Adverse effects reported in anecdotal consumer reports or during clinical studies were first assumed to be due to hydrolytic conversion of CBD to psychotropic Δ9-tetrahydrocannabinol (Δ9-THC) in the stomach after oral consumption. However, research of pure CBD solutions stored in simulated gastric juice or subjected to various storage conditions such as heat and light with specific liquid chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 55 publications
(64 reference statements)
0
40
0
Order By: Relevance
“…The results indicate that for none of the investigated settings for the e-cigarette ∆ 9 -THC could be detected in the obtained condensates by using 1 H NMR spectroscopy. LC-MS/MS measurements have confirmed that an increase in ∆ 9 -THC concentration at the highest energy setting did not occur.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The results indicate that for none of the investigated settings for the e-cigarette ∆ 9 -THC could be detected in the obtained condensates by using 1 H NMR spectroscopy. LC-MS/MS measurements have confirmed that an increase in ∆ 9 -THC concentration at the highest energy setting did not occur.…”
Section: Resultsmentioning
confidence: 85%
“…As a reference sample, the same amount of unvaporized e-liquid was dissolved in 2 ml of MeOD and also prepared for measurement. From each remaining sample solution, which has been obtained from vaporizing the liquids at 0.2 Ω and 200 W, dilutions were prepared for the quantification of ∆ 9 -THC and CBD using a previously described liquid chromatography tandem mass spectrometry (LC-MS/MS) method 9 with the following modifications to improve separation of cannabinoids: separation column Raptor, ARC-18, 2.7 µm, 150*2.1 mm (Shimadzu Deutschland GmbH, Duisburg, Germany). The separation was isocratic with 20% water and 80% methanol, containing 0.1% of formic acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited conversion of CBD to Δ9‐THC in the presence of acid has been suggested to occur in in vitro models (Merrick et al., 2016 ; Bonn‐Miller et al., 2017 ). However, there is no evidence that this transformation occurs in humans in vivo (Nahler et al., 2017 ; Lachenmeier et al., 2019 ; Golombek et al., 2020 ).…”
Section: Limitations and Uncertainties In Scientific Literaturementioning
confidence: 99%
“…E-liquids containing the non-psychoactive cannabidiol (CBD) as well as CBD-rich but ∆ 9 tetrahydrocannabinol (THC)-poor varieties of cannabis are offered for consumption, but depending on the jurisdiction are not allowed to exceed certain thresholds of THC [1][2][3] . Unlike international standards for evaluating tobacco cigarettes, which typically apply routine analytical cigarette smoking machines, the regulatory acceptability of cannabis preparations for vaping or smoking is currently determined by analyzing the e-liquid or the low-THC cannabis in the preparation as it is sold.…”
Section: Introductionmentioning
confidence: 99%